2019
DOI: 10.30845/jesp.v6n3p12
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning Approach for Students with Special Educational Needs: A Systematic Review

Abstract: The paper presents evidence around derived from a systematic review of the literature on the blended learning approach for students with special educational needs. A comprehensive search through multiple known databases identified a dataset of 142 papers from which 22 papers met the criteria for in-depth analysis. The analysis revealed that approach, environment, learner, tools, support and evaluation are categories of extracted in blended learning approach for students with special educational needs. The elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is believed [6,33] that blended learning is a powerful toolkit that allows solving problems that make it necessary to find forms of learning organization that would meet the needs and interests of students.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed [6,33] that blended learning is a powerful toolkit that allows solving problems that make it necessary to find forms of learning organization that would meet the needs and interests of students.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have stressed the potential value of blended care for the daily functioning of people with intellectual disabilities (Frielink et al, 2020; Timmer, 2014; Vereenooghe et al, 2017). However, studies on its use in the field of intellectual disability services have so far been relatively limited and primarily focused on initiatives in therapy and educational settings (e.g., Bell et al, 2016; Cooney et al, 2017; Hronis et al, 2019; Zavaraki & Schneider, 2019). The fact that DigiContact support is generally used in combination with onsite support at home (Zaagsma, Volkers, Koning, et al, 2020) is an example of how blended care can be realised in support settings.…”
Section: Discussionmentioning
confidence: 99%
“…Participants from previous studies on DigiContact (Zaagsma et al, 2019; Zaagsma, Volkers, Koning, et al, 2020; Zaagsma et al, 2021). Included in the analysis were 31 transcripts of interviews with 21 support users (most support users were interviewed twice).…”
Section: Methodsmentioning
confidence: 99%
“…Rivera (2017) has also shown that online supplemental materials can increase cognitive understanding for students with additional needs. A systematic review of the literature on blended and online learning for students with additional needs has shown that computer and network-based technology can improve the performance when used within a blended learning model (Zavaraki & Schneider, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are few high-quality studies found to evaluate the role of blended learning for students with special educational needs (Zavaraki & Schneider, 2019). Available research completed to date shows that blended learning has a number of benefits for both nondisabled and disabled students.…”
Section: Literature Reviewmentioning
confidence: 99%